Inhibition of intrapituitary thyroxine to 3.5.3'-triiodothyronine conversion prevents the acute suppression of thyrotropin release by thyroxine in hypothyroid rats. - Larsen, P R (1979)
Iopanoic acid has been shown to block thyroxine (T4)-5'-monodeiodination in rat anterior pituitary in vitro. To test the hypothesis that the acute decrease in thyrotropin (TSH) after infusion of T4 into hypothyroid rats requires intrapituitary T4 to 3,5,3'-triiodothyroxine (T3) conversion, the effect of iopanoic acid treatment on the generation of nuclear T3 from intrapituitary conversion and the response to TSH were compared in control and iopanoic acid-treated animals. 5 mg/100 g body weight iopanoic acid given 24, 16, and 1.5 h before administration of 125I-T4 reduced the quantity of pituitary nuclear 125I-T3 from local (intrapituitary) T4 to T3 conversion by 60-100%. In association with inhibition of intrapituitary T4 to T3 conversion, there was an increase in the binding of 125I-T4 to the nuclear receptor of the pituitary but the total iodothyronine content of the nuclei was still less than half of the nuclear iodothyronine in control animals. Iopanoic acid did not affect the nuclear/plasma ratio of injected 131I-T3 in the same animals, but did appear to impair 131I-T3 clearance or reduce its distribution volume. Treatment with iopanoic acid did not reduce the quantity of nuclear 125I-T3 in the liver, kidney, or heart of the same animals more than expected from the changes in serum 125I-T3. In control hypo-thyroid animals pretreated with iopanoic acid, the mean TSH was not significantly decreased from the initial value by T4 injection. Iopanoic acid pretreatment did not interfere with the acute TSH response of chronically hypothyroid rats to 70 ng of T3/100 g body weight. These results establish that intrapituitary generations of T3 from T4 is required for the acute decrease in TSH which occurs after T4 infusion. The data also are consistent with the content that it is nuclear binding of the T3 generated from T4 which initiates the inhibition of TSH release.